The behavioural ecology of parasites - Lewis, E. E. (Edwin E.); Campbell, J. F. (James F.); Sukhdeo, M. V. K. (CABI Pub., 2002)
This book addresses the behavioural adaptations of parasites across a broad range of taxa, including parasitoid wasps, entomopathogenic nematodes, seed-feeding insects and plant-parasitic nematodes. The chapters emphasize the fundamental principles of parasitism and address the diversity and sophistication of parasite behavioural adaptations. The chapters are arranged in 4 sections discussing foraging for hosts, host infection, interactions among parasites within hosts and parasite-host interactions.